Isolation and Identification of a Thermostable Amylase-Producing Bacterium from Hatuasa Hotspring - DOMINGGUS MALLE; JUNUS PICARIMA; LAURY CHARA HUWAE; INDRA RAHMAWATI; WAHYU PURBOWASITO (Microbiology Indonesia, 2012)
Hot springs are a common source of thermophyles which produce thermostable enzymes. The objective of this study was to isolate and identify thermostable amylase-producing bacteria from a local geothermal spring. An amylase–producing bacterium strain was isolated from this hot spring which excreted amylase after being grown on starch agar screening plates at 37 °C. It was identified as Bacillus megaterium using the method of 16S ribosomal DNA. The organism is a rod-shape and is a spore-forming  bacterium.  Maximum amylase production was achieved after incubation in the production media for 72 hours. Preliminary analysis of the secreted amylase showed that the enzyme could bind to DEAE-Sepharose matrix and was discharged by eluting with 0.5 M NaCl. The partially purified enzyme was stable up to 75 °C, showing that this enzyme might have potential application in the starch-processing industry.